The relationship between board of directors composition and financial performance of Malaysian public listed companies - Ranjita, Jayakumar (2018)
The issuance of the amended Malaysian Code on Corporate Governance (MCCG) in 2007 clearly shows that continuous efforts have been done by the regulators and policy makers to enhance good governance practices in Malaysia. Based on the MCCG, this study investigated the extent of the corporate governance practices and examined the relationship between corporate governance practices and the performance among Malaysia listed companies. In addition, agency theory is used to explain the corporate governance practices and firms' behavior which is based on the agent's action, and the objective of maximizing time shareholders' wealth. This study covers five corporate governance variables which are expected to have relationship with the financial performance of the company. The five corporate governance variables are number of directors, number of independent directors, firm size, leverage and cash flow. Using a sample of top 100 listed companies in Malaysia for the financial year 2009 until 2012, the findings show firm performance is significantly related to firm size, leverage and cash flow. However, the other two variables which are number of directors and number of independent directors are not significant towards the company performance.